Corruption and International Trade - Agyei, Reinolf (Univerzita Pardubice, 2021)
Corruption has become a roadblock in international trade, where it affects the flow of goods and services between and within countries. International trade deals include a variety of tasks, such as finding a partner, negotiating contracts, and transporting products, all of which have affect trade outcomes and are potentially corruptible. For example, it may be a common practice in some countries for international exporting firms to bribe importing firms as part of forming a business agreement. The main aim of this thesis is to identify the causes and consequences of corruption and determinants of international trade in the case of the V4 countries. The quantitative method was adopted using secondary annual data on Czech Republic, Poland, Hungary and Slovakia from United Nations Conference on Trade and Development (UNCTAD), The World Bank, International Monetary Fund (IMF) and Eurostat. Data on corruption ratings, that is, Corruption Perceptions Index (CPI), was obtained from Transparency International between the year range 2010 to 2019, respectively. With international trade being represented by export rates and import rates. The key findings from this research indicate that corruption negatively affects the export rate in V4 countries; however, its effect on the import rate in V4 countries was different thus;, corruption has a positive effect on the import rate in the V4 countries.
Keywords: vnímání korupce; mezinárodní obchod; dopady korupce; mezinárodní obchod; země V4; corruption perception; international trade; impact of corruption; international trade; V4 countries